Pendampingan Penyuluh Perikanan terhadap Penguatan Kapasitas Kelembagaan Kelompok Perikanan di Kecamatan Cerbon Kabupaten Barito Kuala - Khadijah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The Barito Kuala Regency Government, through its fisheries development program and capacity building program for fisheries extension workers, continues to encourage the improvement of the quality of assistance to fisheries groups, including through the development of information systems, training, and the application of productive and environmentally friendly cultivation technologies. This study aims to analyze the assistance provided by fisheries extension workers to strengthen the institutionalization of fisheries groups in Cerbon District, Barito Kuala Regency. The study was conducted during 2025 in Cerbon District, Barito Kuala Regency, South Kalimantan Province, which was determined purposively because it has active fisheries groups in the cultivation and fishing sectors. The study population was all fisheries groups in Cerbon District, with sampling using a purposive sampling method on groups actively participating in fisheries extension activities. The research data consisted of primary and secondary data analyzed descriptively. Assistance from fisheries extension workers plays an important role in strengthening the institutionalization of fisheries groups in Cerbon District, Barito Kuala Regency. The existence of 16 active fisheries groups indicates that extension and assistance activities can improve the organizational capacity of groups, member cooperation, administrative capabilities, and the development of fisheries and fishing businesses. Government institutional support and ongoing extension programs have contributed to the increased activity of fisheries groups, although challenges remain, such as members' limited technical understanding and limited business capital. More intensive and ongoing support is needed to enable fisheries groups to develop independently, actively, and sustainably.